2009
DOI: 10.1007/s11738-009-0331-2
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress effects on Rubisco in wheat: changes in the Rubisco large subunit

Abstract: The leaf protein pattern from drought-tolerant and drought-sensitive wheat varieties subjected to severe soil drought but with the possibility for recover from stress was studied by two-dimensional polyacrylamide gel electrophoresis (2D-PAGE). The spots representing Rubisco large subunit (RLS) were identified using polyclonal antibodies against Rubisco and immunoblotting. Some qualitative and quantitative differences in the 2D-PAGE protein map of wheat varieties were revealed under drought conditions. Three da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 36 publications
3
65
0
2
Order By: Relevance
“…Our preliminary studies confirmed that a drought period of 7 days produced the most representative and significant results regarding changes in stress-protein content and other physiological parameters. Demirevska et al (2009) determined the degree of water deprivation by analyzing changes in growth parameters of wheat plants and by determining the water deficit from leaf material taken from the same two varieties. In our previous paper it was also established that relative water content of wheat leaves decreased significantly to 24.5% for cv.…”
Section: Resultsmentioning
confidence: 99%
“…Our preliminary studies confirmed that a drought period of 7 days produced the most representative and significant results regarding changes in stress-protein content and other physiological parameters. Demirevska et al (2009) determined the degree of water deprivation by analyzing changes in growth parameters of wheat plants and by determining the water deficit from leaf material taken from the same two varieties. In our previous paper it was also established that relative water content of wheat leaves decreased significantly to 24.5% for cv.…”
Section: Resultsmentioning
confidence: 99%
“…Photosynthesis significantly declined in some plants during the severe water deficit due to the inhibition of biochemical or metabolic (non-stomatal) limitations. It is obvious that water deficit induces some metabolic changes related to protein turnover by increasing protein synthesis, degradation or denaturation (Demirevska et al, 2009). For example, the inactivation of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco, EC 4.1.1.39), the most abundant protein on the earth and a key enzyme in the dark reactions of the Calvin cycle, contributes to the non-stomatal limitation of photosynthesis under water deficit (Lawlor and Cornic, 2002;Demirevska et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility of any plant to drought mainly depends on the degree of stress, different accompanying stress factors, plant species and their developmental stages (Demirevska et al 2009). Drought stress in comparison to other stresses widely affects agricultural crops and finally reduces fresh and dry biomass (Zhao et al 2006;Farooq et al 2009;Shao et al 2009).…”
Section: Morphological and Physiological Responsesmentioning
confidence: 99%